Analisis Sistem Pengendalian Intern Penggajian Dan Pengupahan Pada CV. Surya Sumatera Palembang - Masnoni; Hilwa Anggraini; Roy Saleh; Lia Sari; Nelly (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2019)
This study aims to analyze salaries and wages internal control system at CV. Surya Sumatra Palembang. It is a descriptive study. The technique of analysis used in this study is qualitative method by comparing the implementation of salaries and wages internal control system at CV. Surya Sumatera Palembang with existing theories. The conclusion of the study is the authorization system at CV. Surya Sumatera Palembang is inadequate because there are sums listed in the payroll wich have not verified yet and only authorized by personnel department, that does double duty as payroll administration itself. Procedure which forms the accounting information system at this company seems inadequate. This can be seen in the poor time recording system, there is no supervision of employee attendance list, resulting in employees coming in and out during working hours. Any changes to employee salaries arenot accompanied by a salary change document. The company also has not implemented a proper system of company activities yet, because there is no special section that handles and supervises the presence of employees causing employees lack of discipline. The company should establish the payroll section, cash out slip section and employee salary payment section that carried out by a separate section. The company can choose based on the ability and expertise of each employee so it is created a good corporate organizational structure and to avoid intentional or unintentional fraud. In carrying out activities, CV. Surya Sumatera Palembang should not do double duty. The payroll personnel must be authorized by the personnel department, while cash out slip personnel is authorized by the accounting department, so as to create a good delegation of authority to the company.